Workshop Meningkatkan Kompetensi Guru Melalui Penulisan Artikel Ilmiah Berbasis Penelitian Tindakan Kelas - Minarni, Minarni; Ernawati, M. Dwi Wiwik; Asrial, Asrial; Syahri, Wilda (Jurnal Pengabdian Masyarakat Pinang Masak, 2021)
Quality learning can be made if the teacher has the ability to take advantage of all the potential that exists for the learning carried out. Teachers need pedagogic, social, personal and professional competencies to continuously improve performance and productivity in learning. Writing scientific articles is an activity that cannot be avoided from the current series of teacher activities. As part of efforts to improve the quality of learning and professional competence, teachers must have skills in writing scientific articles, especially those that are ready to be published in journals. Professional teachers can continue to develop through increased education and training in a planned and programmed way, one of which is by writing scientific articles based on classroom action research (CAR). CAR as an alternative to improve learning in the classroom. This study aims to train skilled teachers in making scientific work and train teachers to make CAR research proposals and train teachers to carry out research activities as an effort to develop their profession. Increasing teacher competence in conducting research so that they can analyze and find solutions to learning problems faced by teachers in the classroom. Through this workshop, it is hoped that teachers will have increased competence in implementing, discovering, and implementing learning innovations in the classroom. The implementation of this PTK activity has been carried out at SMAN 2 Sungai Penuh City, Kerinci which consists of teachers and school principals. In the activities given the concept of and implementation of CAR in schools to improve learning improvements and innovations in schools. Teachers can prepare CAR proposals and at the same time conduct research related to learning. For this reason, in order to improve the competence of this teacher, this service activity has been carried out smoothly and the participants gave positive responses. The next target is to be able to publish this activity in the form of proceedings or the Online Journal System (OJS).